Загальні принципи права в діяльності органів конституційного контролю: порівняльно-правовий аналіз - Гриняк, А. Hryniak, A.; Молла, Ю. Molla, Yu. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті з’ясовується значення загальних принципів права при здійсненні конституційного контролю. Прослідковано, яким чином конституційні принципи (основні, загальні, фундаментальні) знаходять застосування в практиці конституційного контролю Франції та Німеччини. Відзначається, що в судовій діяльності зарубіжних держав спостерігається пом’якшення протистояння природно- правових і позитивістських підходів. Пояснюється взаємозв’язок конституційних принципів і правових позицій, які формуються конституційними судами внаслідок інтерпретації основного закону. The article reveals the importance of general principles of law when exercising constitutional control. The article provides information about how constitutional principles (basic, common, fundamental) find use in practice of the constitutional review in France and Germany. The author states that in the judicial systems of the foreign developed countries one can observe mitigation of the confrontation between genuine legal and positivistic approaches to the issues of the constitutional review and explains the relationship of constitutional principles and legal rules that are determined by the constitutional courts on the basis of the main law interpretation. The formation of judicial constitutionalism is considered as a significant factor in the development of modern legal systems. The analyzed situations/cases in which the general principles of law serve as an independent argument of the court decisions are of great importance in protecting the rights and freedoms of citizens.
General Principles of Law in the Activity of the Constitutional Review Bodies: Comparative Legal Analysis
Keywords: принципи права; правова держава; конституційні принципи; природне право; правові позиції; демократія; позитивізм; конституціоналізм; principles of law; constitutional principles; natural law; positivism; legal positions; constitutionalism; democracy; legal state